2019
DOI: 10.1021/acs.jpclett.9b02671
|View full text |Cite
|
Sign up to set email alerts
|

Deep Molecular Orbital Driven High-Temperature Hydrogen Tautomerization Switching

Abstract: Hydrogen tautomerization molecular switches, a promising class of molecular components for the construction of complex nanocircuits, have been extensively studied using low-temperature scanning tunneling microscopy. However, these molecules are generally only reliably controllable in cryogenic environments, obstructing their utility in real devices. Here, we use dispersion-inclusive density functional theory and systematically investigate the adsorption and tautomerization behaviors of porphycene on six transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…Tautomerization is another type of molecular switch 30,31,134–138 . Since the tautomerization process only involves the intramolecular hydrogen atom transfer, it could avoid dramatic structural change during switching.…”
Section: Molecular Switches Based On Tautomerization Of Porphyrin Derivativesmentioning
confidence: 99%
See 4 more Smart Citations
“…Tautomerization is another type of molecular switch 30,31,134–138 . Since the tautomerization process only involves the intramolecular hydrogen atom transfer, it could avoid dramatic structural change during switching.…”
Section: Molecular Switches Based On Tautomerization Of Porphyrin Derivativesmentioning
confidence: 99%
“…The small barrier makes the tautomerization switching sensitive to small thermal disturbances and can only be controlled at low temperatures. Previous experimental observations have demonstrated that the tautomerization temperature is closely related to the strength of the surface–molecule interaction 31,37,138,147 . Therefore, changing the metal surface can adjust the interaction and thereby improving the switching barrier.…”
Section: Molecular Switches Based On Tautomerization Of Porphyrin Derivativesmentioning
confidence: 99%
See 3 more Smart Citations